Associations and Multi-Traits Selection for Identifying Superior and Stable Maize Hybrids (Zea mays L.) Under Tropical Regions - Dedy Supriadi; Yusuf Mufti Bimantara; Yuniel Melvanolo Zendrato; Eko Widaryanto; Kuswanto Kuswanto; Budi Waluyo (Caraka Tani: Journal of Sustainable Agriculture, 2025)
The development of maize hybrids that combine desirable agronomic traits and grain yield could enhance the likelihood of adopting new superior cultivars. Breeding programs that use specific selection criteria aim to produce high-yielding and stable hybrids with good agronomic performance. The study aimed to determine the superior and stable tropical maize hybrids using simultaneous selection based on trait associations. Ten maize hybrids were evaluated across 10 different environments in tropical regions using a randomized complete block design with 3 replications. Genotype, environment, and genotype-by-environment interactions exhibited statistically significant effects on all observed traits, indicating the differential genetic responses among hybrids across environments. Grain yield is significantly associated with agronomic traits and yield components, thus rendering it a suitable selection criterion for identifying superior genotypes. The heritability of each trait was high, along with selection gains, indicating good prospects for selection. Identifying genotypes using multiple traits can be effective for selecting the best genotype based on the selection criteria under multiple environments. H07, H04, and H05 were identified as superior and stable hybrids based on the multi-trait genotype-ideotype distance index (MGIDI) and multi-trait stability index (MTSI), as well as the factor analytic best linear unbiased prediction (FAI-BLUP) and Smith-Hazel. These hybrids can be used in future breeding programs and as candidates for superior tropical maize hybrids.